EDUKASI PENCEGAHAN PENYEBARAN INFORMASI HOAKS MELALUI MEDIA SOSIAL BAGI SISWA DI SMAN 1 PALU - Abdullah Iskandar; Widyatmi Anandy; Irzha Friskanov. S (Jurnal Abdi Masyarakat, 2022)
Social media can be understood that media is a tool used in communication activities. The dissemination of learning information is something that must be considered so that learning activities become more optimal and the objectives of learning can be achieved. The dissemination of information has so far experienced obstacles due to limited communication space. Various social media features used by the community, especially student students, to get learning materials in online learning activities. Fake news or hoaxes are now widely encountered on a daily basis and often even use provocative sensational titles. Based on that description, the problem is what efforts must be made in order to prevent the spread of hoax information with the knowledge and understanding of high school students in filtering information through social media. This service activity provides education to high school students about the importance of knowledge and understanding in preventing the spread of hoax information through social media for everyone. The service location will be carried out at SMA Negeri 1 Palu with the target of school students. The method of implementation is by lectures and discussions.